Евалуација на трансплантационите техники на хируршко лекување на птеригиу и хистоморфолошка проценка на ризик од рецидив - докторска дисертација - Марковска-Челева, Весна (My University, 2012)
Pterygium as an active invasive inflammatory process, a key feature of which is focal limbal failure. The pterygium is a long term and recurrent illness, one that leads to permanent decrease of the visual acuity and anterior segment. Due to the inefficient prophylaxis and the frequent postoperative recurrence, the pterygium is still an intriguing problem in ophthalmology. The aim of the research was to evaluate the success rate of the surgical excision of pterygium with modification of the reconstructive method of liberal conjunctival auto transplantation with grаft from the inferior temporal bulbar conjunctiva, while at the same time to define the advantages and disadvantages of the same, compared to the method of liberal conjunctival auto transplantation with graft from the superior temporal bulbar conjunctiva. The correlation between the stationary and progressive primary pterygium and recurrent pterygium, was determined histopathologically and immunohistochemically by evaluating the fibroblastic proliferation, the degenerative changes of the connective tissue, the angiogenesis, the chronic inflammatory infiltration, the elastosis and the metaplasia of the conjunctival epithelium. Histomorphologically, the structure of the primary pterygia in stationary and progressive stadium, recurrent pterygium and healthy conjunctiva was evaluated. The tear film at the primary stationary and progressive pterygium, and the recurrent pterygium, was evaluated before and postoperative. In the prospective-retrospective study two groups of patients with primary stationary (60 patients) and progressive pterygium (60 patients) were compared, both surgically treated with two different refractive surgical methods of liberal conjunctival auto transplantation with graft from the inferior temporal or superior temporal bulbar conjunctiva. Also, a group of patients (30 patients) with recurrent pterygium was examined and treated with the modified conjunctival auto transplantation with graft from the inferior temporal bulbar conjunctiva. The surgeries were performed at the University Eye Clinic within the Medical Faculty – UKIM in Skopje in the periods of January 2001 to December 2003 and January 2009 to April 2011. The patients were continually followed before and post operatively with Haag-Streit 900 slit lamp to measure the size of the pterygium and to discover its subjective and objective complications and their nature, as well as the incidence of occurrence. Using the Snellen optotype the uncorrected visual acuity before and postoperatively was determined. Furthermore, before and postoperatively the corneal astigmatism was followed with a Javal keratometer and an auto refractometer. Before and postoperatively, the patients were photographed with Topcon Red Camera in the FFA Cabinet at the Eye Clinic. With standard tests for examination of the tear film before and post operatively are followed the patients (90 patients) operated with the modified conjunctival auto transplantation with graft from the inferior bulbar conjunctiva, as well at the Eye Clinic in the period of January 2009 to May 2011. The representative sample of pterygium and healthy conjunctiva were histopathologically, histochemically and immunohistochemically examined at the Institute of Pathology within the Medical Faculty in Skopje in the period of January 2009 to June 2011. A smaller number of early subjective and objective postoperative complications, better visual acuity, decrease of the postoperative astigmatism and smaller number of postoperative recurrence were distinguished at the patients operated with the modified surgical method with graft from the inferior temporal bulbar conjunctiva. Based on the results, the statistical research, as well as on the discussion, the following conclusions were drawn: 1. The modified surgical method with graft from the inferior temporal bulbar conjunctiva proves to be the most successful surgical method for primary stationary and progressive pterygia, as well as recurrent pterygia, based on the following advantages: a) insignificant subjective and objective postoperative complications; b) improvement of the postoperative visual acuity; c) small frequency of recurrence; d) postoperative improvement of the tear functions and the tear film; e) safe, efficient and affordable surgical method; f) outstanding esthetic results; g) preservation of the superior bulbar conjunctiva for future surgical interventions especially recommended for the glaucoma patients. 2. The intensity of the inflammation, the angiogenesis and the degenerative changes, were noted more at the primary progressive and the recurrent pterygia, and are also in correlation with the structure of the pterygium that helps predict the postoperative recurrence and the evolutionary stadium of the pterygium. 3. The correlation between the pterygium and low stability of the tear film was clearly shown by the tear film test results.
Keywords: pterygium; autotransplantaion of conjunctiva; recurrence; immunohistochemical tests of pterygium; dry eye